PLAGIARISME DAN KETIDAKJUJURAN AKADEMIS - Bernadetha Nadeak (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2013)
Academic dishonesty is commonly found in students. There are a lot of factors that play role in this issue such as the perspective of peer group, advanced technology of internet, culture, lack of writing skill, and academic achievement.An effort to establish academic honesty needs involvement of university itself, staff lecturers, and students. This effort is directed to create an atmosphere where academic honesty is an important issue and main concern of the campus.Students need to be informed about academic honesty since they enter university. They needs to be given training to develop their academic writing skills. A special unit to perform this training needs to established in a university. the university also needs to utilize software to check the writing of students in order to detect plagiarism. Keywords : Plagiarism, academic dishonesty, academic skilss